PENDIDIKAN ISLAM DALAM GERAKAN INTELEKTUAL TAREKAT NAQSABANDIYAH SUMATERA BARAT DI ABAD XX - Zainal Zainal (Ta'dib, 2012)
The history of development of Islam in West Sumatera filled with Islamic Education dimension. Several approaches applied by Islamic preachers in West Sumatera are evidences that Islamic Education has been written in the history. The process of Islam development in West Sumatera tends to interact with local social culture and accommodate local tradition and culture emphasizing that educational aspects cannot be separated from history. Consequently, comprehensive understanding upon history is a good step in developing educational quality.Kata kunci: pendidikan islam, sejarah,  gerakan intelektual, tarekat